Echoes of adversity with Voriconazole: a retrospective study - Nandan, Akhila; Palatty, Princy Louis; Govindraj, Laxmi (International Journal of Basic & Clinical Pharmacology, 2025)
Background: Voriconazole is widely used in managing invasive fungal diseases, but its adverse drug reactions, pose significant clinical challenges. This retrospective observational study aimed to evaluate the frequency, severity, and risk factors of ADRs associated with voriconazole treatment in patients in a tertiary care hospital, focusing on demographic characteristics, co-morbidities, route of administration, and trough drug levels. Methods: Data of 95 patients who received voriconazole between 2020 and 2025 were retrieved from electronic medical record. Demographic details, treatment indication, comorbidities, mode of administration, and trough plasma concentrations were collected. ADRs were categorized by system organ class, assessed for severity using modified Hartwig -Siegel scale, and causality was determined using the WHO-UMC system. Statistical analysis employed chi- square tests for categorical variables and Mann–Whitney U tests for trough level comparisons, with p<0.05 considered significant. Results: ADRs occurred in 58 patients (61.1%), hepatobiliary were most frequent (44%). Male patients had a higher ADR rate (54.5%), and those with type 2 diabetes mellitus showed a significantly higher incidence (p=0.008). Cardiovascular comorbidities and thyroid disorders were also significantly associated with ADRs. The intravenous route showed a higher incidence of ADRs compared to oral route. Most reactions were moderately severe (56.8%). A statistically significant relationship was observed between higher trough concentrations and the occurrence of transaminitis. Conclusion: Voriconazole therapy showed a high rate of moderate ADRs, primarily hepatobiliary. Intravenous route and comorbidities-diabetes, cardiovascular disease, and thyroid disorders-were significant risk factors requiring vigilant monitoring.